Relationship between spiritual intellignce, emotional intelligence and marital satisfaction among married audlts in Klang Valley, Malaysia - Tan, Crendy Yen Teng; Tan, Chiu Ying (Universiti Malaysia Sabah, 2018)
Marital satisfaction is one of the important factor for sustaining security, stability, health and successful marriage. It is vital to be studied as 1 divorce case happened in every 10 minutes in Malaysia. The purpose of this study is to examine the relationship between spiritual intelligence, emotional intelligence and marital satisfaction. This study explored these relationships among a sample of 384 married adults in Klang Valley, Malaysia. Respondents completed a set of questionnaires, which included Spiritual Intelligence Self-Report Inventory (SISRI-24), Schutte Self-Report Emotional Intelligence Test (SSEIT) and ENRICH Marital Satisfaction Scale (EMS). The findings indicated that there was a relationship between both intelligence and marital satisfaction.